Development of Geoheritage-based Media Education for Sustainable Development to Improve Ecoliteracy in Elementary Schools - Dewi Nilam Tyas; Desi Wulandari; Aldina Eka Andriani; Sri Sulistyorini (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2025)
The lack of students' ecoliteracy skills due to the absence of appropriate Education for Sustainable Development (ESD)-based learning materials is a significant problem that must be addressed immediately by educators. This study aims to develop and test the feasibility and effectiveness of using ESD-based learning media, in the form of e-modules, to cover the essential material on ecosystems and environmental change. The type of research used is research and development (R&D), with a sequence of potential and problem analysis, data collection, product design, design validation, design revision, product trial, product revision, usage trial, and mass production. Data were collected through tests (pretest and posttest), interviews, observations, and questionnaires. Data analysis employed both descriptive statistics and parametric inferential statistics. The study's results showed that, based on media expert assessments, the level of media feasibility was in the very feasible category, with a score of 92%. Similarly, based on material expert assessments, it was also categorized as very feasible, with a score of 94%. The level of significance obtained was 0.004 on a small scale and 0.00 on a large scale, indicating a statistically significant difference. It can be concluded that the e-module on the Geoheritage of Semarang City has been successfully developed as a sustainable development education medium that is both feasible and effective for use as a learning tool in Elementary Schools. This research product can serve as a learning medium and can be followed up on for further research.